Assessing banks' performance in sustainability practices and programs during the COVID-19 pandemic : The case of Indonesian banks - Robani, Anidah; Farihah, Elva; Hartadinata, Okta Sindhu; Yuliawan, Rahmat (People and Global Business Association, 2024)
Purpose: This study aims to examine the sustainable banking performance within the Indonesian banking sector during the COVID-19 pandemic years of 2020 and 2021. Design/methodology/approach: The study focuses on evaluating the sustainable banking performance of banks listed on the Indonesia Stock Exchange. Secondary data sourced from the banks' official websites, including sustainability and annual reports, were utilized for analysis. Quantitative analysis was conducted through content and statistical analyses. The assessment of sustainable performance is guided by the frameworks provided by the Financial Services Authority and the Global Reporting Initiative. Findings: There is a discernible difference in sustainable banking performance between 2020 and 2021. This variation indicates a discrepancy in bank performance as measured by the Sustainable Banking Index (SBI) between the transitional period for the implementation of the second OJK roadmap in 2020 and after the implementation of the second OJK roadmap in 2021. The presence of the Financial Services Authority's Sustainable Finance Roadmap Phase II further elucidates the sustainable banking performance target. Additionally, the alignment of sustainable finance principles with post-pandemic economic recovery presents an opportunity to rebuild a resilient economy. The positive impacts observed signify an opportunity for the banking sectors to expedite the adoption of sustainable finance. Research limitations/implications: Limitations of this research include reliance on secondary data, with the data gathered limited to the years 2020-2021, and the scope being limited to banks listed on the Indonesia Stock Exchange Nonetheless, the findings suggest that regulatory frameworks promoting sustainability can heighten banks' consciousness toward disclosure and implementation, thereby enhancing their sustainable banking performance. Furthermore, the alignment of sustainability principles with post-pandemic economic recovery presents an opportunity for fostering a resilient economy. Originality/value: This study may be beneficial in enhancing the understanding of sustainable banking practices during times of crisis, shedding light on the importance of regulatory measures and sustainability principles in shaping banks' responses and performance within the Indonesian context. Additionally, the study develops a framework for assessing sustainable banking performance by elaborating on the regulations of the Financial Services Authority (OJK) and GRI guidelines for the banking sector in Indonesia. However, sustainability practices and programs in banks are highly dependent on regional factors, socioeconomic development levels, consumer preferences, and regulatory environments. Therefore, future research may adjust the frameworks according to the conditions of each country.